2011
DOI: 10.1186/1471-2148-11-371
|View full text |Cite
|
Sign up to set email alerts
|

Driving south: a multi-gene phylogeny of the brown algal family Fucaceae reveals relationships and recent drivers of a marine radiation

Abstract: BackgroundUnderstanding the processes driving speciation in marine ecosystems remained a challenge until recently, due to the unclear nature of dispersal boundaries. However, recent evidence for marine adaptive radiations and ecological speciation, as well as previously undetected patterns of cryptic speciation is overturning this view. Here, we use multi-gene phylogenetics to infer the family-level evolutionary history of Fucaceae (intertidal brown algae of the northern Pacific and Atlantic) in order to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
96
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(105 citation statements)
references
References 90 publications
4
96
0
Order By: Relevance
“…This genus is an important component of intertidal seaweed assemblages throughout North Atlantic and northeast Pacific shores, colonizing a range of marine and estuarine habitats. It comprises several accepted species divided into two separate lineages: lineage 1 comprises F. serratus and the F. distichus species complex (including F. gardneri from the Pacific); and lineage 2 contains F. ceranoides, F. vesiculosus and F. spiralis, among other species (Serra˜o et al, 1999;Coyer et al, 2006a;Ca´novas et al, 2011). Fucus species typically grow attached to hard substrata by means of an anchoring holdfast, and can generally be differentiated by a variety of ecological, morphological and sexual characters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This genus is an important component of intertidal seaweed assemblages throughout North Atlantic and northeast Pacific shores, colonizing a range of marine and estuarine habitats. It comprises several accepted species divided into two separate lineages: lineage 1 comprises F. serratus and the F. distichus species complex (including F. gardneri from the Pacific); and lineage 2 contains F. ceranoides, F. vesiculosus and F. spiralis, among other species (Serra˜o et al, 1999;Coyer et al, 2006a;Ca´novas et al, 2011). Fucus species typically grow attached to hard substrata by means of an anchoring holdfast, and can generally be differentiated by a variety of ecological, morphological and sexual characters.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial markers, although often unreliable for determining species relationships in the genus Fucus (Coyer et al, 2006a;Neiva et al, 2010;Ca´novas et al, 2011), indicated that F. cottoniilike forms from the NE Pacific were derived from F. gardneri (Kucera & Saunders, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Two main lineages are apparent within the genus, one consisting of F. distichus L. and F. serratus L. and the other one comprising several species, including F. spiralis L. and F. vesiculosus L., all of which are widespread on shores of the North Atlantic. (Cánovas et al, 2011). Fucus vesiculosus and F. spiralis are closely related and frequently hybridize (Engel et al, 2005), and two new European species within the F. vesiculosus -F. spiralis lineage have been recognized: F. radicans L.Bergstrøm & L.Kautsky from the Baltic Sea (Bergström et al, 2005) and F. guiryi G.I.Zardi, K.R.Nicastro, E.S.Serrão & G.A.Pearson, distributed from Ireland and Britain to the Canary Islands (Zardi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Fucus vesiculosus and F. spiralis are closely related and frequently hybridize (Engel et al, 2005), and two new European species within the F. vesiculosus -F. spiralis lineage have been recognized: F. radicans L.Bergstrøm & L.Kautsky from the Baltic Sea (Bergström et al, 2005) and F. guiryi G.I.Zardi, K.R.Nicastro, E.S.Serrão & G.A.Pearson, distributed from Ireland and Britain to the Canary Islands (Zardi et al, 2011). Fucus radicans has evolved in sympatry with F. vesiculosus after the Last Glacial Maximum in Europe (Pereyra et al, 2009), whereas F. guiryi (F. spiralis-south in Coyer et al, 2011) is a sister species of F. spiralis (Cánovas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation